A spatial approach to combatting wildlife crime - Faulkner, S. C.; Stevens, M. C. A.; Romañach, S. S.; Lindsey, P. A.; Le Comber, S. C. (Conservation biology, 2018)
Poaching can have devastating impacts on animal and plant numbers, and in many countries has reached crisis levels, with illegal hunters employing increasingly sophisticated techniques. We used data from an 8-year study in Savé Valley Conservancy, Zimbabwe, to show how geographic profiling—a mathematical technique originally developed in criminology and recently applied to animal foraging and epidemiology—can be adapted for use in investigations of wildlife crime. The data set contained information on over 10,000 incidents of illegal hunting and the deaths of 6,454 wild animals. We used a subset of data for which the illegal hunters' identities were known. Our model identified the illegal hunters' home villages based on the spatial locations of the hunting incidences (e.g., snares). Identification of the villages was improved by manipulating the probability surface inside the conservancy to reflect the fact that although the illegal hunters mostly live outside the conservancy, the majority of hunting occurs inside the conservancy (in criminology terms, commuter crime). These results combined with rigorous simulations showed for the first time how geographic profiling can be combined with GIS data and applied to situations with more complex spatial patterns, for example, where landscape heterogeneity means some parts of the study area are less likely to be used (e.g., aquatic areas for terrestrial animals) or where landscape permeability differs (e.g., forest bats tend not to fly over open areas). More broadly, these results show how geographic profiling can be used to target antipoaching interventions more effectively and more efficiently and to develop management strategies and conservation plans in a range of conservation scenarios. La caza furtiva puede tener impactos devastadores sobre el número total de plantas y animales, y en muchos países ha alcanzado niveles críticos ya que los cazadores ilegales utilizan técnicas cada vez más sofisticadas. Utilizamos datos de un estudio de ocho años en la Reserva del Valle de Savé, Zimbabue, para mostrar cómo el perfil geográfico - una técnica matemática desarrollada originalmente para la Criminología y que se aplica recientemente en la búsqueda de alimentos y en la epidemiología animal - puede adaptarse para su uso en la investigación de los crímenes faunísticos. El conjunto de datos contenía información sobre más de 10, 000 incidentes de caza ilegal y la muerte de 6, 454 animales silvestres. Utilizamos un subconjunto de datos en el que se conocía la identidad de los cazadores ilegales. Nuestro modelo identificó la aldea local de cada cazador ilegal con base en las localidades espaciales de los incidentes de caza (p. ej.: trampas). La identificación de las aldeas mejoró con la manipulación de la superficie de probabilidad dentro de la reserva para reflejar el hecho de que, aunque los cazadores ilegales viven en su mayoría fuera de la reserva, la mayoría de los incidentes de caza ocurren dentro de la reserva (en términos de criminalística, crimen de cercanía). Estos resultados, combinados con simulaciones rigurosas, mostraron por primera vez cómo el perfil geográfico puede combinarse con datos SIG y aplicarse a situaciones con patrones espaciales más complejos, por ejemplo, en donde la heterogeneidad del paisaje implica que algunas partes del área de estudio tienen una menor probabilidad de ser usadas (p. ej.: áreas acuáticas para animales terrestres) o en donde la permeabilidad del paisaje varía (p. ej.: los murciélagos de los bosques tienden a no volar sobre áreas abiertas). En general, estos resultados muestran cómo el perfil geográfico puede utilizarse para enfocar las intervenciones anti-caza de manera más efectiva y más eficiente y para desarrollar estrategias de manejo y planes de conservación en una gama de escenarios de conservación. 非法捕猎严重威胁着野生动植物的数量。随着盗猎者拥有越来越丰富的经验和技木,非法捕猎在ー些国 家甚至上升成了ー种危机。利用8年间在津巴布韦赛维谷自然保护区收集到的数据,我们展示了起源于犯罪学 而近年来被应用于动物觅食行为学和流行病学研究当中的ー种数学方法一一地缘剖绘，同样能够为野生动植物 犯罪调查提供有力帮助。数据集包含了超过10000次非法捕猎活动及所导致的6454次野生动物死亡事件的信 崖。我们从中抽取了已知盗猎者身份的数据形成ー个子数据集。分析显示，我们建立的模型能够根据非法捕猎 事件发生的空间位置确定盗猎者的居住地(例如陷阱)。虽然盗猎者通常居住在保护区外，但大部分非法捕猎活 动其实发生在保护区内部GIS犯罪学中被定义为通勤犯罪), 针对这一情況,我们可以通过控制保护区内的概率 面来提高识别犯罪者居住地的准确性。这些结果联合严格的模拟分析首次展现了如何将地缘剖绘技术与数 据相结合, 并且应用到分析有更复杂空间模式的犯罪场景当中。例如, 分析区域可利用性有差异(如水域对于陆 地动物很少利用) 的高景观异质性场景, 或者分析区域景观可渗透ÍÉ有差异的场景(例如森林蝙蝠倾向于在开放 空间中活动)0 从更广泛的角度来说这些结果显示地缘剖绘可以在广泛的保护场景中指导我们进行更精准的反 盗猎干预’ 以及指定更有效的管理策略和保护计划。